Microbiota-muscle/immune interactions in rhesus macaque under simulated microgravity revealed by integrated multi‐omics analysis - Peng Zhang; Libin Shao; Jie Zhang; Lu Wang; Xiangsheng Pang; Wuchen Tao; Guangyi Fan; Ling Peng; Guanghan Kan; Wenjiong Li; Xinming Liang; Xin Liu; et al. (Wiley, 2022)
Abstract Background Long‐term exposure to microgravity during spaceflight has adverse effects on human health including muscle atrophy, impaired immune function, and alterations in gut microbiome profile. Gut microorganisms influence a wide range of host biological processes, but their interactions with skeletal muscle and the immune system under microgravity have yet to be elucidated. Methods Rhesus macaques (Macaca mulatta) were subjected to −6° head‐down tilted bed rest (HDBR) for 6 weeks. Faecal samples, skeletal muscle tissue, and peripheral blood mononuclear cells (PBMCs) were collected for metagenomic, metabolomic, and transcriptomic analyses, respectively, and further integrated for a multi‐omics analysis. Results Head‐down tilted bed rest significantly altered taxon abundance (P < 0.05) in 1 class, 5 orders, 11 families, 55 genera, and 122 species of microbes. We also identified the significantly changed metabolites (P < 0.05, fold change >1.2, variable importance in projection >1) in atrophied muscles, including some crucial metabolites (such as l‐alanine and l‐carnitine) and hub metabolites (such as pyridoxamine and epinephrine) involved in energy metabolism. Transcriptomic analysis of PBMCs revealed genes related to leucocyte activation, differentiation, and interleukin‐2 production that were differentially expressed as a result of HDBR exposure (fold change >2 and P < 0.05). By integrating multi‐omics analysis, we identified three bacterial genera (Klebsiella, Kluyvera, and Bifidobacterium) that were closely associated with immune dysfunction and five (including Oligella, Sporosarcina, Citrobacter, Weissella, and Myroides) that were associated with abnormal metabolism of amino acids in atrophied muscles induced by HDBR. The reduced abundance of butyrate‐producing colon bacteria Eubacterium, Roseburia, and their cross‐feeding bacteria Bifidobacteria may contribute to the impaired immune function and muscle atrophy caused by HDBR. Conclusions This is the first report of the HDBR‐associated changes in gut microbiota composition, metabolomics of skeletal muscle, and transcripts of PBMCs in a non‐human primate. The underlying microbiota-muscle and microbiota-immune interactions during simulated microgravity imply that modulation of gut microbiota may represent a novel strategy for enhancing the health and safety of crew members during long‐term space expeditions.